Discipline in Context: Suspension, Climate, and Positive Behavior Interventions and Supports (PBIS) in the School District of Philadelphia, Pennsylvania, 2016-2017 - Gray, Abigail ([Verlag nicht ermittelbar], 2023)
This study is a collaboration between Consortium for Policy Research in Education (CPRE) and the School District of Philadelphia (SDP) that examines the intersection of SDP's Positive Behavior Interventions and Supports (PBIS) initiative with schools' suspension and practices. This study aims to generate new evidence about the effects of schools' disciplinary practices on patterns of student suspension in Philadelphia and inform the alignment of policies with the SDP's shift toward PBIS. This study contributes significantly to the knowledge base about implementing PBIS in fiscally challenged urban districts where exclusionary disciplinary practices have long been used.